Pattern of morphological and neurophysiologic changes in women with the syndrome of the descending perineum - Yu. A. Shelygin; A. Yu. Titov; A. B. Shekhter; A. A. Mudrov; O. M. Birukov; Yu. A. Dzhanayev; M. A. Voynov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To determine morphological rating of connective tissue structures of perineum and detect neurophysiologic disorders of pelvic floor in patients with the descending perineum syndrome (DPS).Material and methods. Original study included 39 women with DPS in the age of 21 to 68 years, with clinical and instrumental signs of descending perineum syndrome. Comparative study of pattern of connective tissue structures in 14 DPS patients that constituted main group and in 10 women without clinical and instrumental DPS signs (control group) was carried out. In 27 DPS patients conductivity of genitofemoral nerve, F-wave latency and anal sphincter motor activity potential were investigated.Results. In main group changes of collagen skeleton of perineal skin, pelvic ligaments, vaginal walls with significant dissociation, disorganization and breakdown of collagen was revealed that was associated by severe hyperelastosis and lymphostasis in connective tissue structures of perineum. In 88,8% of patients with DPS statistically significant disorder of electric conductivity by genitofemoral nerves, and in 70,4% - severe denervation of reflex arch from sacral region of vertebral column to anal sphincter was revealed.Conclusions. Along with distinct changes of connective tissue structures of perineum, DPS it is characterized by neurophysiologic disorders of pelvic floor registered not only in peripheral innervation zone, but also along the whole reflex arch.